The Influence of Competence, Emotional Quotient, and Religiosity on Audit Quality - Ramadhana, Andi Fauziah Aliyya; Hasnawati, Hasnawati (Journal of Business Education and Social, 2022)
The probability that the auditor will assess the presence of an infraction in the client's accounting system and then report that infraction is what we mean when we talk about audit quality. This study aims to analyze the influence of competence, emotional quotient, and religiosity on audit quality. This research is quantitative with convenience sampling. Data was collected using a questionnaire and distributed to respondents using a google form. There were 100 respondents, and 100 of them could be evaluated. The data were processed using SPSS Version 27 for reliability and validity tests and hypotheses using SmartPLS 3.0. The result of this study is that competence and emotional quotient has a significantly positive effect on audit quality. This shows that the auditor should have emotional intelligence, comprehend his or her place in society, and have adequate knowledge in his field to produce better audit quality. Otherwise, the religiosity of an auditor does not influence audit quality. Finally, this study contributes to a better understanding of the influence of competence, emotional quotient, and religiosity on audit quality from auditors in Jakarta.